2014
DOI: 10.1080/15377938.2014.936641
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation Expectations: Individual and Race/Ethnic Group Variation Among an Adult Sample

Abstract: A vignette methodology was used to assess interrogation expectations (IE) among a diverse sample of adults. Vocabulary level, comprehension of Miranda rights, and demographic variables were also assessed. Substantial individual and racial/ethnic group variation in IE was found, with Black participants exhibiting significantly lower expectations of police compliance with Miranda protections compared to White participants. Multiple regression analysis indicated that the combined contribution of vocabulary scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Public perceptions of Miranda rights can be strongly influenced by whether the police are perceived as honoring these rights. Using 12 different vignettes in which the suspects exercised their rights, Johnson et al () asked community and college participants to categorize how the police were likely to respond: (a) honor the assertion of rights; (b) continue questioning; or (c) continue to question and pressure the suspect with threats. Only 18.3% believed that the police officers would always honor the request and stop questioning.…”
Section: Rights Of the Accused: The American Perspectivementioning
confidence: 99%
“…Public perceptions of Miranda rights can be strongly influenced by whether the police are perceived as honoring these rights. Using 12 different vignettes in which the suspects exercised their rights, Johnson et al () asked community and college participants to categorize how the police were likely to respond: (a) honor the assertion of rights; (b) continue questioning; or (c) continue to question and pressure the suspect with threats. Only 18.3% believed that the police officers would always honor the request and stop questioning.…”
Section: Rights Of the Accused: The American Perspectivementioning
confidence: 99%
“…It is well-established that communities of color face disadvantages at all steps of the criminal justice process (Haney-Caron & Fountain, 2021; Kutateladze et al, 2014) and, as a result, parents of color are more likely to prepare their children to have negative interactions with the police (April et al, 2022; Brunson & Weitzer, 2011). In addition, prior research has revealed that Black adults are less likely to believe the police will respect their Miranda rights, which can lead to them waiving their rights out of the belief that they will be ignored or penalized for asserting Miranda (Johnson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This would fit with 'rights' being an abstract term, requiring a year 9 education (about 13-14 years old) to understand (Rogers et al, 2008b). Research with American adults who have been questioned by the police showed only 63 20% believed the police would fully comply with their decision to invoke their legal rights (Johnson et al, 2015). Research is needed to see whether young people have similar expectations of the New Zealand police and if so, may mean young people believe legal rights are given at the police's discretion, which is inaccurate and illegal.…”
Section: Appreciationmentioning
confidence: 99%